A case of psoriasis pustolosa palmaris induced by cetuximab. (18th March 2016) - Marinello, Elena; Pastorelli, Davide; Alaibac, Mauro
Abstract : Cetuximab is a monoclonal antibody that competitively inhibits the epidermal growth factor receptor (EGFR). It is used for the treatment of metastatic colorectal cancer after first-line therapy. We report the first case of a pustular psoriasiform drug eruption induced by cetuximab in a patient with colorectal cancer. This paradoxical side effect could be the result of an imbalance in downstream molecular pathways due to the EGFR signal blockade that could, in selected patients, induce alternative signalling pathways related to keratinocyte proliferation.